Hemangioendothelioma of the eyelid can mimic chalazion - Yasser H Al-Faky; Salem Al Malki; Emad Raddaoui (Oman Journal of Ophthalmology, 2011)
Hemangioendothelioma is an uncommon vascular lesion that usually occurs in the liver, bone, lung, skin, and other organs with unknown etiology. A rare form of this lesion has been reported in the eyelid. We report the case of a 27-year-old female with right lower eyelid mass simulating chalazion of 3 weeks duration. The histopathologic examination of the excised nodule confirmed the diagnosis. To our knowledge, this is the fourth case of eyelid epithelioid hemangioendothelioma reported in the English literature.